Variable optical true-time delay line breaking bandwidth-delay constraints - Petrini, Matteo; Seyedinnavadeh, Seyedmohammad; Grimaldi, Vittorio; Milanizadeh, Maziyar; Zanetto, Francesco; Ferrari, Giorgio; Morichetti, Francesco; Melloni, Andrea (Optics letters, 2023)
Continuously variable true-time optical delay lines are typically subject to a constraint of the bandwidth-delay product, limiting their use in several applications. In this Letter, we propose an integrated topology that breaks the bandwidth-delay product limit. The device is based on multiple Mach-Zehnder Interferometers (MZIs) arranged in parallel, providing easier control and a larger bandwidth compared to ring resonator-based solutions. The functionality of this architecture is demonstrated with a 4-stage delay line by performing measurements in both the time and frequency domains. The delay line introduces a delay of 90 ps over a bandwidth of more than 22 GHz with a negligible group delay distortion, operates on a wavelength range of about 60 nm, and is scalable to a higher number of MZI stages.